A Prospective Validation of Biplanar Ultrasound Imaging for C5-C6 Cervical Medial Branch Blocks. Issue 2 (1st March 2014) - Finlayson, Roderick J.; Etheridge, John-Paul B.; Tiyaprasertkul, Worakamol; Nelems, Bill; Tran, De Q.H.
Abstract : Background: Ultrasound (US) guidance offers an alternative to fluoroscopy for medial branch blocks of the upper cervical spine, but it may be less accurate for blocks at the C5 and C6 levels. We hypothesized that a modified technique using biplanar US imaging would facilitate level identification and provide greater accuracy for the lower cervical spine. Methods: Forty patients with chronic neck pain underwent US-guided blocks of the C5 and C6 medial branches. For each level, 0.3 mL of a local anesthetic/iodinated contrast mixture was injected. Posterolateral in-plane needle placement was carried out in a transverse view, and the position of the needle tip was verified in the coronal plane using the C7 transverse process as a sonographic landmark. Contrast distribution, as assessed by a blinded observer on anteroposterior and lateral x-ray views, constituted the primary outcome. Secondary outcomes were performance time and pain relief 30 minutes after the blocks. Results: One hundred percent and 97.5% of C5 and C6 levels, respectively, demonstrated appropriate contrast distribution. The C7 transverse process was readily identified in the coronal plane in all but 2 subjects. Performance time was 248.8 ± 82.7 seconds; the mean percentage of relief provided by the blocks was 76.9% ± 25.5%. In 30% of patients, a blood vessel was visualized crossing the C6 articular pillar and successfully avoided during needle insertion. Conclusions: Ultrasound guidance using a biplanar approach is a reliable imaging modality for C5 and C6 medial branch blocks.